PENGEMBANGAN INSTRUMEN PENILAIAN PSIKOMOTORIK PADA PRAKTIKUM PEMISAHAN KIMIA - Juli Ana; Masriani Masriani; Rody Putra Sartika; Erlina Erlina; Ira Lestari (Jurnal Education and Development, 2023)
This study aims to determine the feasibility of psychomotor assessment instruments in chemical separation practicum. This research is research and development. This development uses the ADDIE model which is adapted into 3 stages, namely analysis, design, and development. The subject of this research trial involved 8 chemical separation practicum assistants. The data collection instrument used was a feasibility validation sheet and a practicum assistant response questionnaire. The feasibility of the psychomotor assessment instrument in the chemical separation practicum was validated by 3 experts covering the feasibility of content, presentation, and language. Content feasibility obtained an average of 91.67%, presentation feasibility obtained an average of 94.44%, and language feasibility obtained an average of 83.33% with all aspects showing the criteria "Very Eligible". Then the response results of the chemical separation practicum assistant obtained an average of 80.68% with the "Good" criteria. Psychomotor assessment instruments are very suitable for use in the learning process to support the assessment of the results of chemical separation practicum.